Governance Interactions Concerning Peri-Urban Lake Ecosystems: A Systematic Literature Review - Akshay Anand; Yijian Zeng; Diana Reckien; Karin Pfeffer (International Journal of the Commons)
Peri-urban landscapes are urban-rural interfaces that experience challenges due to dynamic urbanisation and climate change effects. These landscapes are also characterized by overlapping jurisdictions, blurred boundaries, and regulatory slippage, leading to diverse and fragmented interactions of governance actors. This is particularly important in the context of peri-urban lake ecosystems, where conflicting goals between governance actors (state to civil society) often result in socio-ecological transformations of lakes. While existing governance studies provide knowledge on actor interactions in urban areas, there is a need to understand interactions between actors in the peri-urban context. To address this gap, we conduct a systematic review to conceptualize governance interactions between actors concerning the governance of peri-urban lake ecosystems. We identify four dominant discourses and their characteristics that may shape forms of lake ecosystem governance. In doing so, we draw insights from the literature review and present a graphical model to illustrate governance actor interactions, contributing to the transformation of lake ecosystems across spatial and temporal dimensions.